(untitled) (Bangladesh Journal of Urology, 2012)
Objective: To evaluate the renal function before and after pyeloplasty using 99mTc-DTPA renography to determine the outcome of pyeloplasty done for pelviureteric junction obstruction. Materials and Methods: This study was done in the department of urology. National Institute of Kidney Diseases and Urology from July 2008 to June 2009. Forty eight patients were included in this study who underwent Anderson Hynes pyeloplasty for pelviureteric junction (PUJ) obstruction. All patients were evaluated with diuretic 99mTc-DTPA renogoam before and at 3 months after operation. Ultrasonography was performed to categorize the severity of hydronephrosis before renography. The outcome of pyeloplasty was evaluated by comparing preoperative and postoperative differential renal function determined by 99mTc-DTPA renogrpahy. Results: Forty eight patients with unilateral hydronephrosis were included in this study. Of these patients 32 male and 16 female with mean age 24.8 years (range 5 years to 42 years). Diuretic renography was done using 99mTc-DTPA in all patients preoperatively and at 3 months postoperatively. Preoperative mean differential renal function was 8.11% (range 0 to 22%) and postoperative mean differential function was 20.48% (range 0 to 42.8%) at 3 months. In 44 (91.67%) case there was significant improvement of renal function where in remaining 4 patients no charge was observed. Conclusion: Renal function improved after Anderson Hynes pyeloplasty regardless the age of the patient at surgery which was determined by 99mTc-DTPA renography. Pyeloplasty performed on patients with relatively better differential function had better results. Bangladesh Journal of Urology, Vol. 14, No. 1, January 2011 p.3-6